Popular or ignored? Archaeological heritage in municipal monuments care programs in Poland - Chabiera, Aleksandra (Folia Praehistorica Posnaniensia, 2025)
This article presents preliminary results from a nationwide survey investigating the inclusion of archaeological heritage in Municipal Monuments Care Programs (MMCPs). The research addresses a significant knowledge deficiency regarding the extent to which archaeological assets are recognized and integrated into local development strategies. Although previous findings indicate that, despite the cultural and historical significance of archaeological heritage, its presence in municipal strategic documents is limited and often superficial, a lack of concrete data makes it impossible to conduct a knowledge-based analysis of the problem. The survey included questions about whether, and in which components of the MMCP, archaeological heritage was present, in order to determine how archaeological heritage is addressed at different stages of the planning process. The study reveals a pronounced gap between the formal recognition of archaeological heritage and its practical implementation in local policy. The results highlight the need for more comprehensive and participatory approaches to heritage management at the municipal level.